Phytoremediation of As, Ag, and Pb in contaminated soils using terrestrial plants grown on Gumuskoy mining area (Kutahya Turkey) - Yildirim, Derya; Sasmaz, Ahmet (Elsevier Science Bv, 2017)
Gumuskoy Ag (As, Zn and Pb) deposits are located about 25 km west of Kutahya, Turkey and one of the largest silver deposits in the country. This study investigated the accumulation and transport of As, Ag, and Pb from the soil into 11 terrestrial plants. Plant and soil samples were collected fromthe field and As, Ag, and Pb content wasmeasuredwith inductively coupled plasmamass spectroscopy. Themean values in the soil, roots, and shoots of the studied plants were, respectively, 4771, 2320, and 1340 mg kg(-1) for As; 35.93, 10.19, and 11.51 mg kg-1 for Ag; and 4180, 1424, and 1050 mg kg(-1) for Pb. The plants collected from the study area were separated into different groups based on the As, Ag and Pb concentrations in plants and their soils. The results showed that Glaucium root, Phlomis root and shoot, Verbascum shoot for As, Glaucium root, Silene root and shoot, Verbascum shoot for Ag and Phlomis root and shoot for Pb could be good a bioaccumulator because of their higher ECRs and ECSs. Therefore, these plants can be useful for cleaning or rehabilitating the soils polluted by Ag, As and Pb. (C) 2016 Elsevier B.V. All rights reserved.
International Conference of the European-Geosciences-Union (EGU) -- APR, 2015 -- Vienna, AUSTRIA
Keywords: Accumulation; Heavy metal uptake; Terrestrial plants; Phytoremediation; Mining area